Immediate and short-term effects of neurodynamic techniques on hamstring flexibility: A systematic review with meta-analysis. - Sergio Núñez de Arenas-Arroyo; Vicente Martínez-Vizcaíno; Ana Torres-Costoso; Sara Reina-Gutiérrez; Bruno Bizzozero-Peroni; Iván Cavero-Redondo (PLoS ONE)
Background Good hamstring flexibility(HF) is crucial for sports performance and health, with injuries having an economic impact on healthcare and sports teams. Therefore, our objectives were to estimate the effect of neurodynamic techniques on HF and to compare the effect of these techniques with static stretching. Methods We systematically searched the Cochrane, MEDLINE(via PubMed), Scopus, Web of Science and Sportdiscus databases for RCTs comparing neurodynamic interventions with control intervention or with static stretching exercises for HF in adults with limited HF. We conducted a random-effects meta-analysis with subgroup analyses according to the type of comparison group(control group or static stretching exercises) and total number of sessions. Furthermore, to reflect the variation in genuine therapy effects in different scenarios, including future patients, we calculated a 95% prediction interval(prI). Results Thirteen trials were included, involving 624 participants. Pooled results showed a significant improvement in HF for immediate (SMD = 1.01, 95% CI: 0.44 to 1.59) and short-term effects (SMD = 1.21, 95% CI: 0.90 to 1.52). Subgroup analyses by type of comparison group showed that these techniques are more effective than the control group in the immediate and short term and than static stretching in the short term. Analyses by total sessions showed a significant increase in HF with a treatment of 1, 3, 10 and 12 sessions. Conclusion Neurodynamic techniques improve HF immediately and in the short term. Subgroup analyses by type of comparison group showed that these techniques are more effective than static stretching in the short term.